Investigation of Microstructural Damage in Ultrahigh-Performance Concrete under Freezing-Thawing Action. (5th April 2018) - Gu, Chunping; Sun, Wei; Guo, Liping; Wang, Qiannan; Liu, Jintao; Yang, Yang; Shi, Tao
Abstract : This work aims to investigate the damage in ultrahigh-performance concrete (UHPC) caused by freezing-thawing action. Freezing-thawing tests were carried out on UHPCs with and without steel fibers. Mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and X-ray computed tomography (X-ray CT) were applied to detect the microstructure of the UHPC matrix before and after the freezing-thawing tests. The results showed that UHPC possessed very excellent freezing-thawing resistance due to its dense microstructure. After the freezing-thawing action, cracks occurred and were prone to initiate at the sand-paste interface in the UHPC matrix. MIP results also indicated that cracks appeared in the UHPC matrix after the freezing-thawing action. The number of defects that can be seen by X-ray CT increased in UHPC after the freezing-thawing action as well. The mismatch of the thermal expansion coefficients of the aggregate and the paste is considered to be the reason for the cracking at the sand-paste interface. The steel fibers in UHPC inhibited the propagation of cracks in the matrix and improved the freezing-thawing performance of UHPC.